(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Natural food seasoning agents are gradually gaining prominence over artificial seasoning agents due to purported side effects, hence, the search for natural food seasoning with functional and improved nutritional quality becomes imperative. This research is aimed at investigating the amino acids composition, fatty acid contents, antioxidant and functional properties of Citrullus vulgaris fermented with mutant and non-mutant strains of Bacillus subtilis to produce ogiri. Bacillus subtilis strains were isolated from spontaneously fermented melon seeds (C. vulgaris) and the B. subtilis isolates were exposed to two different mutagenic agents [Ultraviolet (UV) irradiations and Sodium Dodecyl Sulphate (SDS)] at varying intervals of time to obtain mutant strains. Eight (8) mutated strains of B. subtilis that produced high D-ribose metabolites were used for controlled starter-fermentation of C. vulgaris to produce ogiri. The non-mutant (NMS00) and the market ogiri (RTE00) were included as control samples. The properties mentioned above were determined on the ogiri samples. The most abundant and limiting essential amino acids varied among the ogiri samples. Mutated fermented ogiri samples have improved antioxidant properties. Ogiri sample produced with B. subtilis mutant strain exposed to SDS at 110 sec (MSD51) have the highest monounsaturated fatty acid (MUFA) (15.67±0.00 mg/100 g) and polyunsaturated fatty acids (PUFA) (50.29±0.00 mg/100 g). Free fatty acids and peroxide values are higher in control samples. Modified ogiri produced from the mutant strains of B. subtilis have good functional, amino acids, antioxidant properties and fatty acids. Therefore, may serve as functional condiments with improved nutritional quality.